The socio-ecological impacts of tourism development in the Western Ghats: the case of Wayanad, India - Varghese, Philip; Natori, Yoji (Frontiers in Sustainable Tourism, 2024)
Globally, tourism is advocated as a development tool with the potential to uplift socio-economic conditions for marginalized populations and contribute to biodiversity conservation. The expectation is that the tourism model of development can bring about positive social changes in diverse communities by broadening livelihood opportunities and concurrently preserving crucial ecosystems, which are regarded as valuable assets in the tourism sector. We investigated Wayanad in the Western Ghats of India, challenging the notion of "tourism for development." We examined the socio-ecological features of the region, the evolution of tourism and sustainable tourism, and the implications across various sectors.The research employed an empirical approach grounded in the critical examination of socioecological systems for tourism governance and sustainability. The data were obtained through indepth interviews conducted in Wayanad and a review of the relevant literature. The results reveal that despite the prevalent and persuasive arguments favoring tourism, there are extensive multisectoral implications in tourism development that negatively affect both the environment and people at large. These impacts include the erosion of agrobiodiversity-linked traditional Adivasi lifestyles, the displacement of local communities, the encroachment of tourism projects into forests and increased human-animal conflicts, the absence of social security measures for marginalized communities, a decline in traditional livelihood options, and an overreliance on the tourism industry